Response to a commentary by Barr (2022) on Edoka and Stacey (2020) estimating a cost-effectiveness threshold for healthcare decision-making in South Africa. Issue 8 (28th June 2022) - Edoka, Ijeoma; Stacey, Nicholas
Abstract: Methodological issues pose significant challenges to estimating marginal cost per unit of health. In this commentary, we revisit these challenges and respond to a recent commentary on the validity of previously estimated marginal cost per unit of health in South Africa.